Current Practice of Fluid Maintenance and Replacement Therapy in Mechanically Ventilated Critically Ill Children: A European Survey - Arrahmani, Ismail; Ingelse, Sarah A.; van Woensel, Job B. M.; Bem, Reinout A.; Lemson, Joris (Frontiers in Pediatrics, 2022)
Appropriate fluid management in mechanically ventilated critically ill children remains an important challenge and topic of active discussion in pediatric intensive care medicine. An increasing number of studies show an association between a positive fluid balance or fluid overload and adverse outcomes. However, to date, no international consensus regarding fluid management or removal strategies exists. The aim of this study was to obtain more insight into the current clinical practice of fluid therapy in mechanically ventilated critically ill children. On behalf of the section of cardiovascular dynamics of the European Society of Pediatric and Neonatal Intensive Care (ESPNIC) we conducted an anonymous survey among pediatric intensive care unit (PICU) specialists in Europe regarding fluid overload and management. A total of 107 study participants responded to the survey. The vast majority of respondents considers fluid overload to be a common phenomenon in mechanically ventilated children and believes this complication is associated with adverse outcomes, such as mortality and duration of respiratory support. Yet, only 75% of the respondents administers a lower volume of fluids (reduction of 20% of normal intake) to mechanically ventilated critically ill children on admission. During PICU stay, a cumulative fluid balance of more than 5% is considered to be an indication to reduce fluid intake and start diuretic treatment in most respondents. Next to fluid balance calculation, the occurrence of peripheral and/or pulmonary edema (as assessed including by chest radiograph and lung ultrasound) was considered an important clinical sign of fluid overload entailing further therapeutic action. In conclusion, fluid overload in mechanically ventilated critically ill children is considered an important problem among PICU specialists, but there is great heterogeneity in the current clinical practice to avoid this complication. We identify a great need for further prospective and randomized investigation of the effects of (restrictive) fluid strategies in the PICU.